Trees Outside Forest (TOF): A Nature-based Solution (NbS) and Investment for Climate Resilience - Najima Noushad, Shahina; Ravuther, Shifin S; Nair, Shijith S; Shukla, Gopal; Chakravarty, Sumit (Indian Journal of Agroforestry, 2026)
Trees Outside Forests (TOF) represents a transformative Nature-based Solution (NbS) with the potential to address climate change while delivering diverse ecological and socio-economic benefits. These systems provide critical ecosystem services, including air and water purification, biodiversity conservation, carbon sequestration, and climate regulation. With 31.15 million hectares of TOF coverage, as highlighted in ISFR 2023, India exemplifies the vast potential of these systems to enhance climate resilience. TOF systems are projected to sequester 3.4 gigatons of CO₂ by 2040, making significant contributions to global climate targets, such as limiting warming to 1.5°C or 2°C, as outlined in the IPCC AR6 report. On a global scale, TOF could remove an additional 1–2 gigatons of CO₂ annually, supporting net-zero goals by mid-century. However, barriers such as insufficient planting material quality, inadequate policy frameworks, and limited financial incentives hinder the expansion and adoption of TOF systems. Addressing these challenges requires innovative solutions, including Payments for Ecosystem Services (PES), Minimum Support Prices (MSP) for tree-based products, and certification systems to enhance market access for sustainably produced timber. Strengthening TOF as a core NbS can simultaneously combat climate change, restore degraded ecosystems, improve rural livelihoods, and support national commitments under the Bonn Challenge, Nationally Determined Contributions (NDC), and Sustainable Development Goals (SDGs). This paper positions TOF as a pivotal investment for climate resilience, offering a scalable and impactful strategy for achieving a sustainable and equitable future while addressing the pressing challenges of our time.